Improving the sustainability of global meat and milk production - Salter, Andrew M. (Cambridge University Press, 2017)
Global demand for meat and dairy products has increased dramatically in recent decades and, through a combination of global population growth, increased lifespan and improved economic prosperity in the developing world will inevitably continue to increase. The predicted increases in livestock production will put a potentially unsustainable burden on global resources, including land for production of crops required for animal feed and fresh water. Furthermore, animal production itself is associated with greenhouse gas production, which may speed up global warming and thereby impact on our ability to produce food. There is, therefore, an urgent need to find methods to improve the sustainability of livestock production. This review will consider various options for improving the sustainability of livestock production with particular emphasis on finding ways to replace conventional crops as sources of animal feeds. Alternatives, such as currently under-utilized crops (grown on marginal land) and insects, reared on substrates not suitable for direct consumption by farm animals, represent possible solutions. Coupled with a moderation of excessive meat consumption in wealthier countries, such strategies may secure the long-term sustainability of meat and milk production and mitigate against the adverse health effects of excessive intake.